Evaluation of urinary N-acetyl cysteinyl allyl isothiocyanate as a biomarker for intake and bioactivity of Brussels sprouts - Hwang, E.-S; Jeffery, E.H (Food and chemical toxicology, 2003)
Isothiocyanates (ITC), glucosinolate hydrolysis products from Brussels sprouts (BS) and other cruciferous vegetables, are considered to protect the body from cancer by induction of detoxification enzymes such as quinone reductase (QR). Urinary N-acetyl-cysteine ( NAC) conjugates of ITC have been proposed as biomarkers of crucifer intake. Here we asked if dietary intake and induction of detoxification enzymes are dose-related to urinary NAC conjugate appearance. Male F344 rats (4/group) received an AIN 76B-40 diet containing 0, 10 or 20% freeze-dried BS for 6 days. A human subject ingested 500 g BS. Urinary AITC- NAC was identified in human and rat urine. Ten and 20% BS diets caused a 1.4- and 2.3-fold induction of QR in the pancreas, a 1.5- and 2.5-fold induction in liver and a 3.1- and 3.6-fold induction in colonic epithelium, respectively. Liver and pancreatic QR induction was dose-related, whereas induction of QR in colon was less different between the two doses. Excretion of the conjugate was dose-related only on day 1, and unrelated to dose after day 2. These results suggest that urinary NAC–AITC is a qualitative biomarker for ingestion and bioactivity of BS, but that it may not be dose-related when rats are fed continuously for 2 or more days.